2012
DOI: 10.1088/0960-1317/22/12/125011
|View full text |Cite
|
Sign up to set email alerts
|

ICP polishing of silicon for high-quality optical resonators on a chip

Abstract: Miniature concave hollows, made by wet etching silicon through a circular mask, can be used as mirror substrates for building optical micro-cavities on a chip. In this paper we investigate how ICP polishing improves both shape and roughness of the mirror substrates. We characterise the evolution of the surfaces during the ICP polishing using white-light optical profilometry and atomic force microscopy. A surface roughness of 1 nm is reached, which reduces to 0.5 nm after coating with a high reflectivity dielec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
(39 reference statements)
1
11
0
Order By: Relevance
“…8(a)) and the maximum value is L = 350 μm for D = 550 μm and an etch time of 4 hr. This range for L is approximately seven times larger than previously reported for silicon hemispherical microcavities [1,2,5,7,8]. It was also found that L increases as D increases for a set etch time, where there is at least a 105% increase in L going from D = 100 μm to D = 550 μm.…”
Section: Micromirror Resultsmentioning
confidence: 50%
See 4 more Smart Citations
“…8(a)) and the maximum value is L = 350 μm for D = 550 μm and an etch time of 4 hr. This range for L is approximately seven times larger than previously reported for silicon hemispherical microcavities [1,2,5,7,8]. It was also found that L increases as D increases for a set etch time, where there is at least a 105% increase in L going from D = 100 μm to D = 550 μm.…”
Section: Micromirror Resultsmentioning
confidence: 50%
“…However, there has been little research on tuning α to a specific value, with the exception of a polishing method that uses an inductively coupled plasma etch to increase the radius of curvature of micromirrors after they are wet etched [7]. In terms of the cavity depth, the largest value of L reported for a hemispherical microcavity is 50 μm [7]. Short cavities have largely been pursued previously due to interest in using hemispherical cavities for experiments in cavity quantum electrodynamics, where a small mode volume is desirable.…”
Section: Hemispherical Microcavitiesmentioning
confidence: 99%
See 3 more Smart Citations